Heterogeneous effects of unconventional monetary policy on bond yields across the euro area - Ishak Demir; Burak A. Eroglu; Secil Yildirim-Karaman (University of Lincoln, Lincoln International Business School, Lincoln Economics and Finance Research Group (LEAF), 2021)
This paper investigates the impact of the European Central Bank's unconventional monetary policies (UMP) between 2008-2019 on the European government bond yields. It adopts a novel econometric approach that combines a data-rich factor analysis and VAR with heteroskadasiticy based identification. The results identify a significant and substantial impact for all countries and maturities, but stronger and persistent impact for the periphery. When we decompose the impact into the separate yield components, we find that the UMP decreases the market component for all countries. It decreases the risk-mutualization component for the periphery permanently at the cost of a small increase for the core countries, which provides evidence for the risk-mutualization in the European Monetary Union.
Keywords: C38; E43; E52; E58; F42; G12; 330; unconventional monetary policy; risk-mutualization; cross-country difference; sovereign bond yields; ECB; EMU